Experimental Research of Flow Distribution at Reactor Core Inlet of ACP100 - Ding, Lei; Jiang, Lin; Jiang, Dayu; Zhuo, Wenbin; Yan, Xiao; Xu, Jianjun (Frontiers in Energy Research, 2022)
A 1/3 scaled-down mock-up reactor of ACP100 was used to simulate the flow field in the prototype reactor and to carry out the experiment of core inlet flow distribution. In the mock-up reactor, the major flow path of the reactor is linearly scaled except for the core region which is replaced by 57 dummy fuel assemblies. In addition, the experiment measures core inlet flow rates by a specially designed turbine installed in each dummy fuel assembly. In the experiment, both four-loop balanced and unbalanced operating conditions are tested. The experimental results show that the flow in the major flow path of the mock-up reactor has entered the self-modeling zone and the flow field characteristics are the same as the prototype. The core inlet flow rates of different tests show similar distributions, which all meet the hydraulic performance requirements. Moreover, the effect of impeller rotation on the flow field of the core inlet has also been studied. The study indicates that the flow distribution is almost unaffected by the swirl flow.